Penggunaan Cognitive-Behaviour Therapy Berbasis Internet (ICBT) dalam Penanganan Masalah Perfeksionisme: Systematic Review - Eunike Leonita (Humanitas (Jurnal Psikologi), 2022)
Perfectionism is defined by the overdependence of self-evaluation on the determined pursuit of personally demanding, self-imposed standards in at least one highly salient domain, despite adverse consequences. Perfectionism can affect to certain psychopathologies such as depression, anxiety, and eating disorder. One of the kind interventions that can help this problem is Internet-based Cognitive Behavior Therapy or ICBT for perfectionism which practically using the moduls for CBT. The advantage of ICBT is its flexibility which participant doesn’t need to make an appointment with therapist. This study aims to determine the effectiveness of ICBT through the time (2011-2020), how the implementation did, and the factors that could affect the therapy. The inclusion criteria used were studies on participants with perfectionism; using ICBT interventions; is quantitative research; and research based on research articles or journals. Literature screening was carried out in 3 stages: screening based on title and topic, screening through inclusion criteria, and through assessment of quality. There are 10 journals that have passed this analysis and are used in data synthesis. Based on the analysis conducted, it was found that ICBT was effective in overcoming the problem of perfectionism and was able to significantly reduce perfectionism. This can be seen from the difference in results between the pre-test and post-test as well as these results managed to survive when followed-up. ICBT itself provides advantages in terms of time, effort, and cost efficiency in therapy as well as flexibility to be applied anywhere.